Mechanical response of taper dental implants using finite element analysis. Issue 2 (August 2020) - Jain, Vinamra; Dommeti, Vamsi Krishna; Nutu, Emil; Merdji, Ali; Biswas, Jayanta Kumar; Roy, Sandipan
Abstract: Implants have created a great impact in the bio medical industry. There are different kinds of dental implants which are existing in the market. Every implant has a unique feature and withstands for different time period. This study on the dental implant creates a new model which includes the porous and tapered angle. Titanium alloy was used for making the implant and supporting bone tissue was considered. Computed tomography data were used to generate the mandible model. In the analysis both static and dynamic loading condition were considered. Three dimensional FEM was performed on the implant to find out the mechanical response for this specific type of implant. The von-Misses stress were calculated for implants and it was observed that safe when compared with yield strength of implant and abundant. In analysis it was also varied bone quality for cortical and cancellous bone and the effect of stress produced can be predated before the implantation done for the patients.